Analysis of the impact of SMEs' production output on Kazakhstan's economic growth using the ARDL method - Aziza Syzdykova; G. Ž. Azretbergenova (Economies, 2025)
Small and medium-sized businesses (SMEs) are an essential subject of economic activity in any country because, without their participation, the development and formation of the very structure of the economy are almost impossible. The role of SMEs is significant since these businesses allow for an increase in the number of jobs, develop competition, and, as a result, improve the quality of goods, creating different price segments. More than 4 million people are employed in this sector in the Republic of Kazakhstan, and their share of GDP is 36.7%. The accelerated contribution of the SME sector to Kazakhstan's GDP has led to the need to conduct a study in this area. This study analyzes the impact of SME production output on Kazakhstan's economic growth by considering some macroeconomic variables using the ARDL model. The study's findings confirm that SME output positively and significantly impacts economic growth. The government of Kazakhstan has been implementing a series of policies and incentive programs to increase the contribution of the SME sector to economic growth since the years of independence. However, SMEs are not able to reach their full potential due to various restrictions that limit their expansion. This study offers some suggestions for the development of the SME sector. In order to ensure SME concentration in the economy, investment in R&D should be a priority incentive. On the other hand, we should recognize the shadow economy problem in the country.
Keywords: 330; SME; SME output; Kazakhstan; economic growth; ARDL method